The economic burden of chronic diseases: estimates and projections for China, Japan, and South Korea - Bloom, David E.; Chen, Simiao; Kuhn, Michael; McGovern, Mark E.; Oxley, Les; Prettner, Klaus (NBER working paper series on historical factors in long run growth, 2017)
We propose a novel framework to analyse the macroeconomic impact of noncommunicable diseases. We incorporate measures of disease prevalence into a human capital augmented production function, which enables us to determine the economic costs of chronic health conditions in terms of foregone gross domestic product (GDP). Unlike previously adopted frameworks, this approach allows us to account for i) variations in human capital for workers in different age groups, ii) mortality and morbidity effects of non-communicable diseases, and iii) the treatment costs of diseases. We apply our methodology to China, Japan, and South Korea, and estimate the economic burden of chronic conditions in five domains (cardiovascular diseases, cancer, respiratory diseases, diabetes, and mental health conditions). Overall, total losses associated with these non-communicable diseases over the period 2010-2030 are $16 trillion for China (measured in real USD with the base year 2010), $5.7 trillion for Japan, and $1.5 trillion for South Korea. Our results also highlight the limits of cost-effectiveness analysis by identifying some intervention strategies to reduce disease prevalence in China that are cost beneficial and therefore a rational use of resources, though they are not cost-effective as judged by conventional thresholds